2019
DOI: 10.29333/iji.2019.12117a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Model of Student Field Practice at Faculty of Tarbiyah and Teaching Training in Indonesia: A Reality and Expectation

Abstract: The assessment model of student field practice is essential to assess the achievement of students' competence as a prospective teacher. It is also important in Faculty of Tarbiyah and Teaching Training. The objective of this research is to identify the available assessment model in sequence to find causes why do the lecturers find difficulty in assessing the students' practice and the expected remedies. This research used concurrent mixed method with concurrent triangulation design. Data was collected using qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Based on several experts' opinions about evaluation (Adnan et al, 2019;Andrade, 2019;Chen, 2017;Gu, 2020;JH & Baderiah, 2020;Ratminingsih et al, 2018;Wirawan et al, 2018;Yahiji et al, 2019;Yudianto et al, 2019), it can be concluded that evaluation is an activity planned to assess the achievement of a program for decision making. In addition, it is stated by Republic of Indonesia Law Number 20/2003 article 57 paragraph (1) on the National Education System that evaluation is carried out in order to control the quality of education nationally as a form of teachers' and institutions' accountability to interested parties.…”
Section: Discussionmentioning
confidence: 99%
“…Based on several experts' opinions about evaluation (Adnan et al, 2019;Andrade, 2019;Chen, 2017;Gu, 2020;JH & Baderiah, 2020;Ratminingsih et al, 2018;Wirawan et al, 2018;Yahiji et al, 2019;Yudianto et al, 2019), it can be concluded that evaluation is an activity planned to assess the achievement of a program for decision making. In addition, it is stated by Republic of Indonesia Law Number 20/2003 article 57 paragraph (1) on the National Education System that evaluation is carried out in order to control the quality of education nationally as a form of teachers' and institutions' accountability to interested parties.…”
Section: Discussionmentioning
confidence: 99%
“…Learning activities can be appropriately designed by utilizing the results of students' assessment (Yahiji et al, 2019). Formative assessment, in particular, is really important for both students and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…These indicated that teachers did not intensively do as what they believed. Therefore to be effective, teachers need further training including guidelines revision, monitoring and periodic evaluation (Yahiji, Otaya, & Anwar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of various kinds of techniques aims to show the effectiveness of the assessment and the achievement of the students (Brown & Race, 2013). The guidelines provide the instrument used in assessing students, which is relevant to the curriculum change and response to the learning outcome (Yahiji et al, 2019). It also informs about the techniques for assessing the three domains of students' competencies.…”
Section: Assessment Policy In the Indonesian Higher Educational Contextmentioning
confidence: 99%